A high-quality chromosome-scale genome assembly of the Cherokee rose (Rosa laevigata) - Yi Wang; Huijun Yan; Xianqin Qiu; Hao Zhang; Yonghong Zhang; Hongying Jian (Scientific Data)
Abstract Rosa laevigata is an excellent rose germplasm, highly resistant to aphid, and immune to both rose black spot and powdery mildew disease. It is also a well-known edible plant with a long history of medicinal use in China, having the effects of improving kidney function, inhibiting arteriosclerosis, and reducing inflammation. In this study, we assembled a high-quality chromosome-scale genome for R. laevigata by combining Illumina, PacBio, and Hi-C data, which has a length of approximately 494.2 Mb with a scaffold N50 of 68.6 Mb. A total of 493.2 Mb (99.8%) of the draft genome sequences were anchored on seven pseudochromosomes and two gapless pseudochromosomes were included in the final genome assembly. A total of 37,117 protein-coding genes were predicted, 34,047 of which were functionally annotated. Repeat annotation revealed 659,558 (285.6 Mb) repeat elements, accounting for 57.8% of the genome. The chromosome-scale genome provides valuable information to facilitate comparative genomic analysis of rose family and will accelerate genome-guided breeding and germplasm improvement of both R. laevigata itself and modern roses.